Evaluation of a game-based training course to build capacity for insecticide resistance management in vector control programmes - Dormann, Claire; Duda, Kirsten; Hamainza, Busiku; Yewhalaw, Delenesaw; Hemingway, Charlotte; Coleman, Marlize; Coleman, Michael; Thomsen, Edward (PloS one, 2020)
Across Africa, malaria control programmes are increasingly challenged with the emergence of insecticide resistance among malaria vector populations. Confronted with this challenge, vector control staff must understand insecticide resistance management, think comprehensively and react positively when confronted with new problems. However, information on the subject is often only available through written guidelines that are difficult to put into practice. Based on the successes and strengths of educational games for health, we developed and evaluated a novel game-based course to fill the gap in training resources for insecticide resistance management. The training was evaluated by analysing results of pre- and post-course knowledge tests and self-efficacy surveys, as well as post-course interviews. At the start of the training, fundamental concepts of insecticide resistance were reviewed through Resistance101, a mobile app game. Subsequently, insecticide resistance management strategies were explored using the simulation game ResistanceSim, which was introduced by mini-lectures and complemented by class discussions and group work. The game-based training was conducted and evaluated in two African countries (Ethiopia and Zambia) using a mixed-methods approach. Quantitative outcome measures included knowledge acquisition and change in self-efficacy. We completed a qualitative inductive thematic analysis of participant interviews to explore the views and experiences of participants with the games and training, and the impact of the training on professional practices and attitudes. The game-based training increased knowledge in the short-term and improved self-efficacy scores. The training increased participants' knowledge base, stimulated knowledge sharing and changed work practices. The game-based training offers scalable training opportunities that could nurture and capacitate the next generation of professionals in vector control.